TRANSMISSION TO REFLECTION TRANSFORMATION OF TELESEISMIC WAVEFIELDS - Kumar R.M.; Bostock M.G. (My University, 2006)
In this paper we review the transformation of P and SV transmission Green's functions into the corresponding reflection quantities for one-dimensional, elastic media at precritical slownesses. To obtain estimates of the transmission Green's functions from observed data, we apply a recently developed approach that exploits the minimum-phase nature of the direct waves and employs autospectra and cross-spectra of raw component seismograms representing multiple sources recorded at a single station. To accomplish transformation to reflection Green's functions, we outline a practical recipe that involves amplitude balancing, energy normalization, cross correlation, and removal of free surface effects. We assess its performance through application to both synthetic seismograms and data from station Hyderabad. In all cases we are able to identify the first-order scattering contributions from the continental Moho. The transmission-to-reflection transformation has potential applications for imaging hitherto elusive shallow mantle discontinuities, since interfering forward and back scattering contributions are effectively separated by component in the resulting reflection Green's functions. Copyright 2006 by the American Geophysical Union.